The Impact of the Transition towards a Renewable Energy Economy to Achieve Diversification of the Algerian Economy (Analytical and forward-looking approach) - Bouchelaghem, Amirouche; Bouguerra, Karima (Finance and Business Economies Review, 2021)
The aim of this study is to foresee and identify the impact of the shift towards the exploitation of solar energy in Algeria as an important source for diversifying the Algerian economy by looking at the resource curse that it is currently suffering from.It has been concluded that solar energy is not expected to become a new curse for Algeria due to the small expected revenue of solar energy, and that oil and natural gas will remain in the future in Algeria,more importantly, the possibility that Algeria may struggle to diversify the economy in the field of alternative energy.